Pre-validation study of alternative developmental toxicity test using mouse embryonic stem cell-derived embryoid bodies. (January 2019) - Lee, Jae-Hwan; Park, Seon Young; Ahn, Changhwan; Kim, Cho-Won; Kim, Ji-eun; Jo, Na Rae; Kang, Hee Young; Yoo, Yeong-Min; Jung, Eui-Man; Kim, Eun Mi; Kim, Ki-Suk; Choi, Kyung-Chul; et al.
Abstract: The embryoid body test (EBT) is a developmental toxicity test method that assesses the half inhibitory concentrations of substances in the area of embryoid bodies (EBs), and in the viability of mouse embryonic stem cells (ESCs) and fibroblasts (3T3 cells) following chemical exposure for three and four days, respectively. In the previous study, the EBT showed more advanced than the embryonic stem cell test (EST) from the European Centre for the Validation of Alternative Methods (ECVAM) applying cardiac differentiation of mouse ESCs, because the EBT greatly reduced the exposure time, labor, and amount of materials required, and misclassification of embryotoxic potential. This pre-validation study evaluated the predictive accuracy of the EBT using 26 coded test substances by two steps: intra-laboratory and inter-laboratory reproducibility tests. Since some substances have different embryotoxic potentials at different pregnancy periods, in this study, a new prediction model consisting of non-toxic and toxic classes was used, instead of the existing prediction model assessing embryotoxicants in four classes. The results of the intra- and inter-laboratory tests were highly accurate (above 80%) when substances were classified using the predictive model. In conclusion, EBT can accurately classify various embryotoxicants in a short time with less effort and greater validation. Highlights: The experiment was conducted to verify the embryo body test (EBT) method. Predictive models were created for two classifications (non-toxic and toxic). Experimental results showed high accuracy (above 80%). EBT can be used to classify embryotoxicants in the short term.